El arte de la seda en el Mediterráneo medieval - Navarro Espinach, Germán (En la España Medieval, 2004)
A detail study of techniques and rhythms of silk manufacture in Mediterranean workshops, with particular attention to fifteenth-century Valencia. Bibliographic exposition of the state of research. Sytematic analysis of Valencian documentation regarding the cultuvation of silkworms, processes of spinning, twisting, and dying silk, types of cloth and production costs.
Keywords: Silk Silk cloth Textile techniques Valencia Medieval Mediterranean Fifteenth Century